Checklist of helminths found in Patagonian wild mammals - Fugassa, Martin H. (Zootaxa, 2015)
Using available reports, a checklist of the recorded helminth parasites of wild mammals from Patagonia was generated. Records of parasites found in Patagonia were included, together with records from mammals in áreas outside of Patagonia but whose range extends into Patagonia. Information about the host, localities, and references were also included. A total of 1323 records (224 Cestoda, 167 Trematoda, 894 Nematoda, 34 Acanthocephala, and 4 Pentastomida) belonging to 452 helminth species (77 Cestoda, 76 Trematoda, 277 Nematoda, 21 Acanthocephala, and 1 Pentastomida) found in 57 native mammals (22 Rodentia, 4 Didelphimorphia 1 Microbiotheria, 7 Chiroptera, 5 Cingulata, and 13 Carnivora) were listed. However, only 10.6 % of the reports were conducted on samples from Patagonia and corresponded to 25% of mammals in the region. In addition, many studies were made on a few species and, for example, 52% corresponded to studies made on Lama guanicoe. This suggests the need to increase efforts to know the parasitic fauna in a peculiar region as is the Patagonia. This is the first compilation of the helminth parasites of mammals in Argentine Patagonia and is important for parasitological and paleoparasitological studies.